Relapse of skull osteoma after hydroxyapatite cement cranioplasty: Case Report - Yang, Xiang; Liu, Yanhui; Zhang, Yuekang (Frontiers in Oncology, 2023)
In this case report, we present an extremely rare and previously unreported case of skull osteomas relapse without any attachment to the skull after hydroxyapatite cement (HAC) cranioplasty. The 49-year-old male patient was admitted with recurrence of the left frontal skull lesion, he underwent craniectomy and HAC cranioplasty for a left frontal osteoma before 14 years. Intraoperative findings disclosed multiple irregular lesions locating on the HAC flap without any attachment to the bony structure and the roots of the lesions originating from the outer layer of the dura through several reserved holes. Pathological diagnosis was osteoma. The purpose of this report is to document this rare occurrence and provide the most probable pathogenesis for this rare event.